PENGARUH KOMPENSASI, MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI (Studi kasus pada Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Kendal) - Devi Indriastuti, 15.05.51.0242; Rahayuningsih, sri (Students' Journal of Economic and Management, 2019)
The purpose of this research was to determine the effect of Compensation, Motivation and Leadership on Employee Performance. The object of this research was conducted at the Department of Public Works and Spatial Planning in Kendal Regency. The sampling technique in this research used purposive sampling with the number of respondents 140 people. Data collection is done through questionnaires deployment. Data analysis techniques used include validity test, reliability with alpha coefficient (Alpha cronbach), multiple regression analysis, T test to test and prove the research hypothesis. The results showed that Compensation had a positive and significant effect on employee performance, the greater the compensation obtained by the employees, the higher the performance of employees. Motivation has a positive and significant effect on employee performance, the greater the motivation in the employee, the higher the performance of employees in the department. Leadership has a positive and significant effect on employee performance, the higher the leadership, the higher the performance of employees to achieve the targets to be achieved each year.